Factors Associated With Skeletal Dysplasia In Fetus Of Pregnant Women Attended At The Maternal Perinatal National Institute In Lima From June 2009 To September 2016 - Ingar-Pinedo, Jaime (2017)
Objective. To determine the factors associated with skeletal dysplasia in fetuses of pregnant women attended at theNational Maternal Perinatal Institute of Lima from June 2009 to September 2016. Materials and methods. Observational,retrospective, cross-sectional, case-control study. The sample size was 328 pregnant women. For the cases, 82 clinicalrecords of pregnant women whose fetus presented an ultrasound diagnosis of skeletal dysplasia were reviewed and 246clinical records were reviewed of patients whose fetus did not present any fetal malformation, keeping The ratio betweencases and controls of 1: 3.